2019
DOI: 10.1002/14651858.cd012777.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal ultrasound for diagnosing abdominal tuberculosis or disseminated tuberculosis with abdominal involvement in HIV-positive individuals

Abstract: BackgroundAccurate diagnosis of tuberculosis in people living with HIV is difficult. HIV‐positive individuals have higher rates of extrapulmonary tuberculosis and the diagnosis of tuberculosis is often limited to imaging results. Ultrasound is such an imaging test that is widely used as a diagnostic tool (including point‐of‐care) in people suspected of having abdominal tuberculosis or disseminated tuberculosis with abdominal involvement.ObjectivesTo determine the diagnostic accuracy of abdominal ultrasound for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…Our study questions the value of abdominal US in VL diagnosis as part of routine care in VL suspect patients. It remains to be further assessed whether the procedure would be useful in HIV patients with suspected VL, as concurrent tuberculosis has been reported to be very common in this group and US could contribute to the diagnosis of disseminated or abdominal tuberculosis [ 23 ]. Comparative studies in Ethiopia and Sudan would also shed light on the discrepancies in findings seen in our and reported studies from Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…Our study questions the value of abdominal US in VL diagnosis as part of routine care in VL suspect patients. It remains to be further assessed whether the procedure would be useful in HIV patients with suspected VL, as concurrent tuberculosis has been reported to be very common in this group and US could contribute to the diagnosis of disseminated or abdominal tuberculosis [ 23 ]. Comparative studies in Ethiopia and Sudan would also shed light on the discrepancies in findings seen in our and reported studies from Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…tuberculosis is very low from ascitic fluid [ 3 ], thus a composite reference standard (CRS) was used in the study. The CRS was broadly based on published guidelines and previous categorizations for ATB and comprised of clinical, radiological, microbiological and biochemical findings associated with ATB patients and response to ATT ( Fig 2 ) [ 3 , 22 , 38 ]. Based on the CRS, the patients were categorised into ‘Definite’ ATB, ‘Probable’ ATB, ‘Possible’ ATB and ‘Non-TB’ groups ( Fig 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…‘Possible’ ATB category (n = 13) included patients who presented with chronic symptoms of ATB with either radiology suggestive of ATB (palpable abdominal mass or omental thickening) or an abnormal chest X-ray (consolidation, calcification or pleural effusion) or presence of other features as described in Fig 2 . [ 3 , 4 , 22 , 38 ]. However, in this group, the information about response to ATT was not available because either the patient got lost to follow up (n = 11) or left against medical advice (n = 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent Cochrane metanalysis including HIV-positive adults, FASH signs predicted tuberculosis with a moderate diagnostic performance only. The authors also concluded that ultrasound results should be considered in combination with other tests, such as chest X-ray and Xpert MTB/RIF® only [10]. No randomized controlled trial evaluating sonography for the diagnosis of tuberculosis has been done yet.…”
Section: Introductionmentioning
confidence: 99%